Review for Status and Challenges of Mongolia’s Agricultural Sector in terms of Research and Extension System - 이창근; 김한성; 주용식 (한국국제농업개발학회지, 2020)
This research aims to identify the status quo of Mongolia's agricultural research and extension, as well as defining the sector's key challenges. Given that the agricultural sector in Mongolia is the culture itself for the country's rural communities, it is a driving force of employment for rural households. However, the sector has been losing its momentum since the nation's transition to a free market economy in the 1990s. While investment in Mongolia's agricultural research and extension remains at a very low level due to a number of challenges, this research focuses on bridging the gaps between farmers and researchers, to help realizing the nation's agricultural growth potential.
Keywords: Mongolia; Agricultural Sector; Research; Extension; Collaboration